1372-P: Micro and Macro Complications Three-Year Follow-up in LANDMARC—Longitudinal Nationwide Study on Real-World Outcomes of Type 2 Diabetes in India - RAIS, NADEEM; DAS, ASHOK K.; JOSHI, SHASHANK R.; MITHAL, AMBRISH; KALRA, SANJAY; GOPALAKRISHNAN UNNIKRISHNAN, AMBIKA; THACKER, HEMANT; SETHI, BIPIN; CHOWDHURY, SUBHANKAR; SUGUMARAN, AMARNATH; SATPATHY, ASHWINI; GADEKAR, ARVIND; et al. (Diabetes (New York, N.Y.), 2023)
Microvascular and macrovascular complications were evaluated during the 3 years (yrs) of LANDMARC, a prospective observational study (CTRI/2017/05/008452) that included participants with T2D on ≥2 antihyperglycemic medications. Out of 6222 evaluable participants (mean baseline age: 52.1 yrs, T2D duration: 8.6 yrs and A1C: 8.05%), 5273 participants completed the 3-yr follow-up. The mean A1C decreased by 0.68% (p<0.0001) in 3 yrs. Microvascular complications were noted in 18.02% (1121/6222) of participants, while the incidence of macrovascular complications was 3.29% (205/6222). Neuropathy was the most commonly reported complication (baseline: 11.8% and 3-yrs: 14.8%). The 3-yr results indicate slightly higher complications among those who were overweight, but the difference was non-significant (p=0.8380); and significantly higher complications among those with suboptimal glycemic control (p<0.0001) or having CV risk factors (p<0.0001) (Table). The most common macrovascular complication was MI. A total of 37 CV deaths were reported, with majority being sudden deaths (n=24), followed by fatal myocardial infarction (MI, n=10), coronary artery procedure (n=2), and stroke (n=1). These results offer insights into disease progression and suggest the need for controlling risk factors and timely treatment adjustment in participants with T2D.